The Case of Kinta Bateri Sdn. Bhd. - Othman, Mohd Zainudin (1998)
The case srudy is divided into two parts. Part one of the case facts that include the introduction to the background of the company and the probable cause of the problem that the company faced. Part two, is the case analysis, involving the diaJssion based on the methodology used, problem solving, include the used of the SWOT analysis in identifying the company strenght, weakness, opportunity and threat. The strategies are develop for the company can choose and implement in order to overcome the problems. Finally the used of the SPACE (Stra1egic POSitioning and Action Evaluation) Model to detemine the strategy direction that the company should follow for it future growtn.